Determination of the best quail eggs using simple additive weighting - Abadi, Satria; Huda, Miftachul; Azmi Jasmi, Kamarul; Shakib Mohd. Noor, Sulaiman; Safar, Jimaain; Kilani Mohamed, Ahmad; Hassan Wan Embong, Wan; Marzuki Mohamad, Ahmad; Hehsan, Aminudin; Basiron, Bushrah; Suhaila Ihwani, Siti; Maseleno, Andino; et al. (International Journal of Engineering and Technology, 2018)
Eggs are livestock products contributed greatly to the achievement of the nutritional adequacy of the public; the egg is a food that is very good for children who are growing because it contains nutrients such as a complete protein, fat, vitamins and minerals that are easy to digest. One of the eggs are much in demand by children are quail eggs. The nutritional value of quail eggs is not less than the nutritional value of eggs containing 12.8% protein and 11.5% fat. Quail eggs are good quality will have good nutritional value anyway. To determine the quality of a good quail eggs will require an expert system. The method used in determining the quality of a good quail eggs using Simple Additive weighting method. The criteria in this research that egg size, style/color of the shell, the shell thickness, shell texture, shape and cleanliness of quail eggs. With the expert system is expected to assist farmers in determining the quail eggs quail egg quality so that the people can consume quail eggs that have good nutritional value. The results of this study showed an alternative ranking first in C with a value of 0.95, ranking second D with a value of 0.7208, ranking third E with a value of 0675, ranking the fourth A with a value of 0.4542 and ranking last in the B with a value of 0.4541.Â Â